Developing the Basketball Community: Supporting Outdoor Basketball Courts Social and Community Interactions (UK) - Connor Russell; Haydn Morgan; Natalie Campbell (International Journal of Basketball Studies, 2023)
Participation in informal sport practices (such as pick-up basketball) has been demonstrated to have positive impacts on essential life skills, such as confidence, communication, resilience, and teamwork. However, an essential feature in supporting and sustaining participation in sport is the quality of the facilities that participants can practice upon, a factor that is more pronounced for informal sport practices. Utilising a qualitative methodological approach and employing semi-structured interviews (n=22), this paper examines the impact of a series of basketball court renovations that were undertaken in London (United Kingdom) on the development of basketball-focused outcomes (e.g. skill development) but also on wider individual and community development. Findings revealed that the court renovations, and the free access to play on them, not only enabled basketball players to enhance their skills, but also supported the benefits of physical activity on physical and mental health, while creating opportunities to develop and broaden social networks.